2006
DOI: 10.1086/507978
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Primordial Stars in a ΛCDM Universe

Abstract: Primordial stars are formed from a chemically pristine gas consisting of hydrogen and helium. They are believed to have been born at some early epoch in the history of the Universe and to have enriched the interstellar medium with synthesized heavy elements before the emergence of ordinary stellar populations. We study the formation of the first generation of stars in the standard cold dark matter model. We follow the gravitational collapse and thermal evolution of primordial gas clouds within early cosmic str… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

58
737
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 488 publications
(799 citation statements)
references
References 156 publications
58
737
4
Order By: Relevance
“…Simulations of the collapse of primordial molecular clouds (Bromm et al, 1999(Bromm et al, , 2002Abel et al, 2000;Yoshida et al, 2006;Gao et al, 2007) suggest that the first generation of stars contained many 'very massive stars' (VMSs) with m > 100 M . This is because of the slow subsonic contraction -a regime set up by the main gas coolant, molecular hydrogen -further fragmentation into sub-components is not seen (although it is not clear if this is a numerical effect, rather than due to the gas physics, see Glover et al, 2008).…”
Section: Population III Remnantsmentioning
confidence: 99%
“…Simulations of the collapse of primordial molecular clouds (Bromm et al, 1999(Bromm et al, , 2002Abel et al, 2000;Yoshida et al, 2006;Gao et al, 2007) suggest that the first generation of stars contained many 'very massive stars' (VMSs) with m > 100 M . This is because of the slow subsonic contraction -a regime set up by the main gas coolant, molecular hydrogen -further fragmentation into sub-components is not seen (although it is not clear if this is a numerical effect, rather than due to the gas physics, see Glover et al, 2008).…”
Section: Population III Remnantsmentioning
confidence: 99%
“…One potential pathway is the collapse of a primordial, i.e., metal-free, "normal" star into a stellar-mass black hole. Earlier numerical simulations performed to study the formation of the first generation of stars (Abel et al 2002;Bromm et al 2002; ⋆ Corresponding author: latif@iap.fr Yoshida et al 2006) suggested that the masses of the first stars are of the order of a few hundred solar. However, recent simulations found that the protostellar disk forming in the minihalo fragments into multiple clumps (Clark et al 2011;Greif et al 2012;Stacy et al 2012;Latif et al 2013b; and leads to the formation of multiple stars.…”
Section: Introductionmentioning
confidence: 99%
“…These 3 σ+ perturbations over the background dark matter density field virialized by redshifts of z ∼ 20-50 (Tegmark et al 1997;Abel et al 2002;Bromm et al 2002). With few exceptions (e.g., Turk et al 2009), these simulations suggest that the gas pooling into the halos underwent a quasi-hydrostatic contraction until they had sufficient mass to trigger runaway gravitational collapse (Abel et al 2002;Bromm et al 2002;Bromm & Loeb 2004;Yoshida et al 2006; O'Shea & Norman 2007; Yoshida et al 2008). These studies estab-⋆ e-mail: alexander.desouza@gmail.com, basu@uwo.ca lished the standard paradigm that the progenitor cloud cores of the first stars were most likely to have been massive and formed in relative isolation.…”
Section: Introductionmentioning
confidence: 87%